The Law and the Stateless society: A Legal Case for Entrepreneurship in Government Services - de Siqueira Bentes, Lucas (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2020)
This paper presents the main attributes of the law with regard to the development and prosperity of an economy, following the principles set forth by the Austrian School. The law has an intrinsic nature with the market economy and yet is ignored by its researchers. The libertarian legal theories allow us to fully understand that since its inception, the law is a means of structuring the behaviors of individuals. And the stronger and spontaneous were its institutions, the more the society thrived. Nevertheless, the State significantly weakened the pillars of the law, seizing its foundations and making itself its sole operator, rotting its most vital roots. We must treat the State as a player in the vast market of government. In so doing, it will be responsible for its mistakes because only competition in a huge market can drive a nation to prosperity with the right laws.